Epigenetic age acceleration and methylation differences in IgG4-related cholangitis and primary sclerosing cholangitis - Alexandra Noble; Rodrigo Motta; Silvia Cabras; Belen Moron Flores; Jan Nowak; Aleksandra Glapa-Nowak; Alessandra Geremia; Jack Satsangi; Emma Culver (Clinical Epigenetics)
Abstract Background IgG4-related cholangitis (IgG4-SC) and primary sclerosing cholangitis (PSC) are chronic fibro-inflammatory hepatobiliary conditions, with genetic, environmental, and immunologic risk factors, in which epigenetic alterations may provide insights into pathophysiology and novel biomarkers. This study is the first to assess methylation signatures in IgG4-SC. Results Whole blood DNA methylation profiling and genotyping was performed in 264 individuals; 47 with IgG4-SC, 65 with PSC, 64 with ulcerative colitis (UC), and 88 healthy controls. We identified 19 significant methylation differences between IgG4-SC and controls and 38 between PSC and controls. IgG4-SC and PSC shared 8 probes. Inflammatory genes (including CEP97, IFNAR1, TXK, HERC6, C5orf36, PYY, and MTRNR2L1) were predominantly involved in dysregulated methylation. Epigenetic age acceleration was observed in patients with IgG4-SC, but not in those with PSC or UC. meQTL analyses to identify genetic determinants of methylation revealed a strong human leucocyte antigen (HLA) signal in both PSC and IgG4-SC (HLA-DQB2, HLA-DPA1, HLA-F and HLA-DRA). Conclusions We identify novel epigenetic alterations in IgG4-SC and PSC, with biological age acceleration in IgG4-SC, providing insights into disease pathogenesis, and highlight the role of genetic variation especially within the HLA region in shaping the methylome.